ENTITAS KEBERAGAMAN DALAM SEMANGAT KEBANGSAAN: KAJIAN SOSIOKULTURAL - Lingga, Thomson R; Heni Haryani; Sirait, Asnita (JURNAL KEBANGSAAN RI, 2024)
The pluralistic existentialist harmonization is built on the basis of the construction of fundamental values because of the need for each individual to interact and relate unconditionally. A reflection of the wisdom of diversity that is rooted and stimulates various fundamental meanings in national life in the midst of a pluralistic community because of encounter. The basic value of diversity is realized and connected in one understanding and an element of openness from interpersonal limitations in realizing the usefulness of the spiritual values of life are constructed in awareness of the need to create and work. The existence of awareness of diversity is manifested in the practice of togetherness because the transparent knitting of basic socio-cultural values (ethics socio-cultural values) and the basic needs of every individual (the basic needs of human life) always emits a beautiful panorama towards the awakening of the horizon of national patriotism. The emanation of these values becomes self-actualization amidst the various forms and realities of the need to achieve a common goal (the social purposeful life).